Molecular discrimination of tall fescue morphotypes in association with Festuca relatives - Talukder, Shyamal K.; Azhaguvel, Perumal; Chekhovskiy, Konstantin; Saha, Malay C. (PloS one, 2018)
Tall fescue (Festuca arundinacea Schreb.) is an important cool-season perennial grass species used as forage and turf, and in conservation plantings. There are three morphotypes in hexaploid tall fescue: Continental, Mediterranean and Rhizomatous. This study was conducted to develop morphotype-specific molecular markers to distinguish Continental and Mediterranean tall fescues, and establish their relationships with other species of the Festuca genus for genomic inference. Chloroplast sequence variation and simple sequence repeat (SSR) polymorphism were explored in 12 genotypes of three tall fescue morphotypes and four Festuca species. Hypervariable chloroplast regions were retrieved by using 33 specifically designed primers followed by sequencing the PCR products. SSR polymorphism was studied using 144 tall fescue SSR primers. Four chloroplast (NFTCHL17, NFTCHL43, NFTCHL45 and NFTCHL48) and three SSR (nffa090, nffa204 and nffa338) markers were identified which can distinctly differentiate Continental and Mediterranean morphotypes. A primer pair, NFTCHL45, amplified a 47 bp deletion between the two morphotypes is being routinely used in the Noble Research Institute's core facility for morphotype discrimination. Both chloroplast sequence variation and SSR diversity showed a close association between Rhizomatous and Continental morphotypes, while the Mediterranean morphotype was in a distant clade. F. pratensis and F. arundinacea var. glaucescens, the P and G1G2 genome donors, respectively, were grouped with the Continental clade, and F. mairei (M1M2 genome) grouped with the Mediterranean clade in chloroplast sequence variation, while both F. pratensis and F. mairei formed independent clade in SSR analysis. Age estimation based on chloroplast sequence variation indicated that the Continental and Mediterranean clades might have been colonized independently during 0.65 ± 0.06 and 0.96 ± 0.1 million years ago (Mya) respectively. The findings of the study will enhance tall fescue breeding for persistence and productivity.